2022
DOI: 10.1108/jicv-06-2022-0022
|View full text |Cite
|
Sign up to set email alerts
|

The verbiage in variable message signs and traffic diversion during crash incidents

Abstract: Purpose WIth limited research on the effects of variable message sign (VMS) message content and verbiage on revealed driver behavior, this study aims to investigate how different verbiage of crash-related messages are related to the diversion rate. Design/methodology/approach Using ordered logit models, the associations of message verbiage with diversion rates during crash incidents were assessed using five years of VMS message history within a section of I-15 in the state of Utah. Findings A significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Other studies have found that verbose and irrelevant messages conveyed via VMS have a significant impact on the diversion rate. Acharya and Mekker found that the verbiage of a crash-related message can increase the diversion rate of drivers (36). The combination of information content with the highest increase in diversion rate was miles to crash + ''Prepare to Stop.''…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found that verbose and irrelevant messages conveyed via VMS have a significant impact on the diversion rate. Acharya and Mekker found that the verbiage of a crash-related message can increase the diversion rate of drivers (36). The combination of information content with the highest increase in diversion rate was miles to crash + ''Prepare to Stop.''…”
mentioning
confidence: 99%
“…Other studies have found that verbose and irrelevant messages conveyed via VMS have a significant impact on the diversion rate. Acharya and Mekker found that the verbiage of a crash-related message can increase the diversion rate of drivers ( 36 ). The combination of information content with the highest increase in diversion rate was miles to crash +“Prepare to Stop.” However, displaying irrelevant information on a VMS might result in important traffic management messages not being effectively communicated to drivers ( 16 ): compliance with a detour message was significantly lower when preceded by irrelevant messages on the VMS.…”
mentioning
confidence: 99%